Benzophenones from African plants to fight cancers and cancer drug resistance - Nchiozem-Ngnitedema, Vaderament-A.; Buyinza, Daniel; Kuete, Victor (Elsevier, 2025)
In response to the cancer threat, several interventions have been sought including the search for small molecules from natural sources that may arrest cancer at any of its different cycle stages. Such molecules include the benzophenones from fungi or higher plants (Clusiaceae and Guttiferae families). This book chapter will systematically cover the emerging areas in the field of benzophenones and their polyprenylated benzophenone analogs isolated from herbal medicines found in Africa with application in cancer treatment. Initially, benzophenones have been introduced as chemical entities, then an overview of their biosynthesis has been introduced, followed by phytochemical characterization from various tissues in the plant kingdom, and lastly a comprehensive updated study on benzophenones and their prenylated derivatives against various cancer cell lines has been provided.